Separation and characterization of alpha-chain subunits from tilapia (Tilapia zillii) skin gelatin using ultrafiltration. (1st December 2015) - Chen, Shulin; Tang, Lanlan; Su, Wenjin; Weng, Wuyin; Osako, Kazufumi; Tanaka, Munehiko
Highlights: Alpha-chain subunits of tilapia skin gelatin could be separated by ultrafiltration. The α1 -subunit was separated from gelatin by regenerated cellulose membrane. The α2 -subunit was separated from gelatin by polyethersulfone membrane. The T g of α1 -subunit was higher than that of α1 -subunit during the first DSC scan. Reduced viscosity of α1 -subunit was higher than that of α2 -subunit below 16 °C. Abstract: Alpha-chain subunits were separated from tilapia skin gelatin using ultrafiltration, and the physicochemical properties of obtained subunits were investigated. As a result, α1 -subunit and α2 -subunit could be successfully separated by 100 kDa MWCO regenerated cellulose membranes and 150 kDa MWCO polyethersulfone membranes, respectively. Glycine was the most dominant amino acid in both α1 -subunit and α2 -subunit. However, the tyrosine content was higher in α2 -subunit than in α1 -subunit, resulting in strong absorption near 280 nm observed in the UV absorption spectrum. Based on the DSC analysis, it was found that the glass transition temperatures of gelatin, α1 -subunit and α2 -subunit were 136.48 °C, 126.77 °C and 119.43 °C, respectively. Moreover, the reduced viscosity and denaturation temperature of α1 -subunit were higher than those of α2 -subunit, and the reduced viscosity reached the highest when α-subunits were mixed with α1 /α2 ratio of approximately 2, suggesting that α1 -subunit plays a more important role in the thermostability of gelatin than α2 -subunit.